The Rhetoric of Bliss: Linguistic Approaches to Ambivalence in Hindu Spiritual Language - Dwivedi, Amitabh Vikram (Entrepalavras, 2025)
This paper explores the ambivalent attitudes toward religious ecstasy in contemporary India and throughout history, focusing on how language structures and shapes the discourse surrounding intoxicants and religious ecstasy. Through a linguistic analysis centered on semantic and lexical meaning, the paper examines the language used in key texts, including the Rig-Veda, and others. It employs cross-cultural and intertextual analysis to describe ecstasy and its associated taboos, focusing on rhetoric, metaphors, and structures. The study investigates the consumption and offerings of intoxicants, such as Soma, Sura, and others, as both taboo and revered forms of drug-induced spirituality and religious objects. It examines the deities for whom intoxicants are beloved religious objects and offerings, and explores Hindu traditions—particularly Tantric sub-sects of Shaivism and Shaktism, as well as Ayurvedic practices—where herbs, minerals, and alcohol or drug-induced ecstasy are seen as means to cleanse and heal the soul. Additionally, it addresses accounts that portray alcohol and drug-induced ecstasy as taboo, particularly in gender and caste-related contexts where intoxicant consumption leads to joyful, foolish, and generally debauched experiences of sensorial new worlds. The paper reveals how the language used in these texts reflects and constructs the ambivalence surrounding these practices. It shows how linguistic choices both shape and are shaped by cultural and religious attitudes toward intoxicants.